Automatic control system for the concentration of ingredients from vegetable raw materials using liquefied CO2 - I. X. Siddikov, Sh. I. Fayziev, K. Kh. Gafurov; U. M. Ibragimov (International Journal of Advanced Science and Technology, 2020)
The article deals with the creation of an ARS the concentration of extract from vegetable raw materials. Mathematical models of extraction process and technical means of control system are developed. To stabilize the given concentration value, a fuzzy PI-regulator is proposed, which allows considering changes in the load and the environment. A quick-operating algorithm for adaptive adjustment of fuzzy PI controller parameters is proposed. Simulation modeling was carried out to check the adequacy of the taken results. Comparative analysis showed that the proposed algorithm has more significant qualitative indicators than classical ones.